Smoothing properties of the fractional Gauss-Weierstrass semi-group in Morrey smoothness spaces - Franka Baaske; Romaric Kana Nguedia; Hans-Jürgen Schmeißer (AIMS Mathematics)
In this paper we derive caloric smoothing estimates in Morrey smoothness spaces using decomposition techniques by means of wavelets and molecules. Our new estimate extends results for Gauss-Weierstrass, Cauchy-Poisson and fractional Gauss-Weierstrass semigroups.